2017
DOI: 10.1016/j.gexplo.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemical characteristics of a volcanic-sedimentary aquifer with special emphasis on Fe and Mn content: A case study in Mexico

Abstract: Previous studies performed on the volcanic-sedimentary aquifer of the Tenancingo Valley (Mexico) reports high concentrations of Fe, Mn, and NO 3 − , and water from several wells receives purification treatments due to presence of Fe and Mn. These studies have not achieved conclusive results regarding the origin of Fe and Mn, nor have hydrogeochemical evaluations of the aquifer been performed. The present study aimed to evaluate the physicochemical characteristics of the water and identify the geochemical proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…If the halite solution is responsible for the presence of Na + , this molar ratio is approximately 1 [37]. On the other hand, if the value of this ratio is >1, it can be assumed that Na + is released from a weathering reaction with silicates [18], with an ion-exchange process [22,38]. In the current studied area, the Na + /Cl − molar ratio varied from 1.268 to 1.861, with an average of 1.616, which means that all samples show Na + release as a result of a silicate weathering reaction process, as demonstrated by hydrochemical facies.…”
Section: Binary Ratios and Geochemical Processesmentioning
confidence: 99%
“…If the halite solution is responsible for the presence of Na + , this molar ratio is approximately 1 [37]. On the other hand, if the value of this ratio is >1, it can be assumed that Na + is released from a weathering reaction with silicates [18], with an ion-exchange process [22,38]. In the current studied area, the Na + /Cl − molar ratio varied from 1.268 to 1.861, with an average of 1.616, which means that all samples show Na + release as a result of a silicate weathering reaction process, as demonstrated by hydrochemical facies.…”
Section: Binary Ratios and Geochemical Processesmentioning
confidence: 99%
“…Stability diagrams of Ca-Al, Na-Al, Mg-Al, and K-Al silicate phases are useful to study the occurrence of incongruent dissolution (e.g., [ 41 , 44 ]). Figure 6 a shows that most water samples are found in the limit between the stability field of kaolinite and Ca-Montmorillonite, and some samples are located in the Ca-montmorillonite, Na-montmorillonite and Mg-smectite fields, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Natural sources come from weathering of minerals (pyroxenes, amphiboles, biotite, magnetite and in particular, olivine). While, anthropogenic sources come from wastewater discharge, dust and aerosols during metallurgical processing, coal combustion, corrosion of water pumping infrastructure and transport of minerals or contamination associated with mining activities (Esteller et al, 2017). The main factors controlling the presence of these elements in water are pH, redox conditions and presence of organic or inorganic ligands (Corniello and Ducci, 2014).…”
Section: Groundwater Assessment For Drinking Purposementioning
confidence: 99%
“…The main factors controlling the presence of these elements in water are pH, redox conditions and presence of organic or inorganic ligands (Corniello and Ducci, 2014). An acidic pH indicates that both ions are mobile, while a more neutral pH indicates that mobility is determined by redox conditions (Esteller et al, 2017). The Table 4 shows that A2 and A5 have direct correlation with pH value (acid) so could be concluded that Mn source comes from anthropogenic not by redox conditions.…”
Section: Groundwater Assessment For Drinking Purposementioning
confidence: 99%